Impacts of ideological trends of renaissance architecture on royal garden design of Qing Dynasty, China: a Lowland and Wetland case of the Old Summer Palace (Yuan Ming Yuan) - X. M. Zhao; Y. Lu; J. R. Shi; H. Liu; Y. Chen; Z. Wang; K. Hokao (International Association of Lowland Technology, 2017)
Planning and design methodology of residential areas in ancient time is a comprehensive transition of technology and aesthetics, where imperial palatial projects play an exemplary role. Through the process of the Age of Discovery, European culture infiltrated into China's architectures, especially the royal gardens and palaces in Qing Dynasty. Ideological trends of Renaissance architecture present a diverse phenomenon into Chinese palace design of Yuan Ming Yuan. The Old Summer Palace buildings were analyzed in terms of their components such as column, dome, sculpture and decoration, door and wall, the proportion of elements, etc. The results prove that the cultural phenomenon is a convergence of and technology and aesthetics between European and Chinese.